The relationship between technostress and job satisfaction amongst secondary school teachers in Klang, Selangor / Nur Soleha Saiful Azman - Saiful Azman, Nur Soleha (2024)
The inclusion of technology in secondary school education has revolutionized teaching methods in the past few years. This has opened up new possibilities but has also presented notable difficulties. These challenges stem from increased administrative duties, limited time because of technology integration, and reduced job fulfilment due to the quick implementation of new technologies without sufficient assistance. This research aims to investigates the correlation between technostress and job satisfaction in secondary school teachers in Klang, Selangor. Utilizing a mixed-method approach and multistage cluster sampling, data were gathered to investigate the relationship across 6 secondary schools involving 85 respondents in this study. The results reveal that there is no significant overall correlation between technostress and job satisfaction, although there are weak links between specific aspects of technostress and job satisfaction. The implications of this study are valuable for educational institution management and leadership practices, especially in the areas of technostress management and improving teacher job satisfaction. Managing technostress is identified as crucial for enhancing teacher well-being and satisfaction. Potential strategies include providing training in technology management, establishing clear work-life boundaries, and fostering a supportive school environment. In summary, focusing on technostress management is key to improving teacher satisfaction and wellbeing. Future research could further explore another variables or factors for technostress and job satisfaction, taking into consideration variations in teacher demographics and school environments.